2009
DOI: 10.1063/1.3253712
|View full text |Cite
|
Sign up to set email alerts
|

An oxide thermal rectifier

Abstract: We have experimentally demonstrated thermal rectification as bulk effect. According to a theoretical design of a thermal rectifier, we have prepared an oxide thermal rectifier made of two cobalt oxides with different thermal conductivities, and have made an experimental system to detect the thermal rectification. The rectifying coefficient of the device is found to be 1.43, which is in good agreement with the numerical calculation.Comment: 4 pages, 4 figures, Appl. Phys. Lett. (in press

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
213
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(222 citation statements)
references
References 14 publications
(29 reference statements)
8
213
0
1
Order By: Relevance
“…with different temperature dependent thermal conductivities which fit well with a theoretical model based on Fourier's law [38]. Their results also showed that conduction was greater in the direction of high to low thermal conductivity.…”
Section: Later In 2009 Kobayashi Et Al Experimentally Demonstrated Tsupporting
confidence: 65%
See 1 more Smart Citation
“…with different temperature dependent thermal conductivities which fit well with a theoretical model based on Fourier's law [38]. Their results also showed that conduction was greater in the direction of high to low thermal conductivity.…”
Section: Later In 2009 Kobayashi Et Al Experimentally Demonstrated Tsupporting
confidence: 65%
“…to think about what devices can be fabricated, what quantities can be measured and whether the theoretical [15] Al/SS thermal warping 0.67 Rogers [17] Al/SS thermal potential barrier 0.1 Powell et al [19] Al/SS thermal warping 0 Clausing [20] SS/Al thermal strain 0.2 Lewis and Perkins [21] Al/SS thermal warping 0.41 O'Callaghan et al [27] varied thermal warping 0.13 Stevenson et al [23] varied thermal warping 0.21 Chang et al [5] CNT and BNNT non-uniform mass loading 0.034 Kobayashi et al [38] varied bulk thermal conductivity 0.18 [4] 1D chain nonlinear lattice 0.33 Li et al [81] 1D chain nonlinear lattice 0.98 Hu et al [82] 1D chain nonlinear lattice 1.0 Lan et al [75] 1D chain nonlinear lattice 1.0 Hopkins and Serrano [88] 1D chain asymmetric mass loading and defect 0.29 Yang et al [48] graphene asymmetric ribbons 0.6 Hu et al [49,55] graphene asymmetric ribbons 0.47 Alaghemandi et al [42,44] CNT non-uniform mass loading 0.17 Hu et al [79] water/silica interface transmission 0.21 Roberts and Walker [74] argon/krypton interface transmission 0.13 Wu and Li [46] CNH asymmetric CNT 0.55 Yang et al [47] CNC asymmetric CNT 0.46 Wu and Li [56] CNT CNT interface 0.39 systems can be realized in the lab. In fact, experimental study of thermal rectification is said to be ongoing in quite a few research labs.…”
Section: Quantum Thermal Systemsmentioning
confidence: 99%
“…Inspired by these theoretical and simulation studies, the solid state thermal rectifier were realized in various macroscopic systems, 177 and the rectification ratio was enhanced remarkably. Very recently, Tian et al demonstrated the thermal rectification ratio up to 21% in trapezia shaped bulk graphene oxide.…”
Section: A Thermal Rectification In Nanostructuresmentioning
confidence: 99%
“…3.1 were systematically exploited to build rectifiers [77], using two cobalt oxides with different thermal conductivities. The vicinity of a structural phase transition could be used to enhance the tempera-ture dependence of the thermal conductivity [78] and the asymmetry of the shape has been exploited to vary the spatial dependence of κ(x, T ) [128].…”
Section: Building An Actual Thermal Rectifiermentioning
confidence: 99%